MANAJEMEN PEMBIAYAAN DANA BOS DI MADRASAH - Ilhami, Id’ha (Universitas Nurul Jadid, 2020)
The purpose of this study was to see how the financing management at Madrasah Tsanawiyah Mathla'ul Anwar Kedondong, Pesawaran Regency, Lampung. This study used a descriptive qualitative approach with data collection techniques, interviews, observation and documentation. Data analysis was performed using reduction techniques, data display and conclusion drawing. Triangulation test is used to test the validity of the data. The results showed: 1). Planning (budgeting) at MTs Mathla'ul Anwar begins with compiling the RKAM through the mechanism of madrasah plenary meetings, identifying madrasah admission plans, identifying madrasah expenditure plans, compiling RAPBM, ratifying RAPBM by the foundation. 2). Implementation (accounting/ bookkeeping) uses a cash book known to the principal of the madrasah and refers to technical instructions. 3). The assessment (auditing) is conducted internally by the principal and externally by the government (Depag, Kanwil Kemenag, Inspector General Kemenag